Evaluation of Character Education Program Based on School Culture - Hary Murcahyanto; Mohzana Mohzana (Sumber Belajar Sejahtera, 2023)
This study aims to describe the context, input, process, and product of a character education program based on school culture. The research design used is an evaluative model. Oral and written data were obtained from interviews, observation, and documentation techniques. The analysis uses 4 stages, namely, data display data reduction and conclusion drawing. Text and discourse interpretation techniques with critical hermeneutic methods. The results and conclusions of this study are Context evaluation aspects which include components of program planning, needs analysis, and determination of program implementation objectives have been carried out well, but in terms of determining the priority of the main values and the stage of socializing the priority of the program's main values, it is not optimal. Aspects of evaluation Input include components of standard qualifications for principals, program design, qualifications of educators and education staff, and support from parents and guardians, curriculum development at the education unit level has been carried out well, but the carrying capacity of infrastructure is still inadequate. Aspects of product evaluation and internalization of the main values of character education have shown good results.